Humanizing education for a better Muslim: an expectation from an ICT Perspective - Zainol, Zaini (Kulliyyah of Economics and Management Sciences, 2021)
This chapter tries to understand and reflect ‗ibadah camp and its connection with the whole process of humanizing education especially from the information, communication, and technology (ICT) perspective. Various spirituals were laid out for the three or four days programme with the main objective is to nurture and remind all participants (murabbi) on their roles and duties regardless of their current position in the university. Specifically, like academia, regardless of academic background, we must discharge the duty by the way we talk, we dress, we behave, we mingle, we participate and we perform our tasks and religious duty to Allah SWT